The Effect of Rice Washing Water Concentration and Growing Media Composition on the Growth and Yield of Tomato Plants (Solanum lycopersicum L.) - Sinaga, Daniel Carlos Pinondang; Rumbiak, Julio Eiffelt Rossaffelt; Utama, Putra; Firnia, Dewi (Sam Ratulangi University, 2026)
Tomato (Solanum lycopersicum L.) production in Banten has significantly declined due to land constraints and suboptimal cultivation practices, necessitating sustainable alternatives like fermented rice wash water (RWW) and optimal planting media. This study aimed to determine the most effective combination of RWW concentration and growing media composition to enhance tomato growth and yield in polybag cultivation. The research was conducted from November 2025 to March 2026 at Universitas Sultan Ageng Tirtayasa, Banten, using a factorial Randomized Complete Block Design. Factors included RWW concentrations (0, 50, 100, and 150 mL/L) and four media compositions (soil; soil+manure; soil+husk charcoal; and soil+manure+husk charcoal).The results showed that the soil-only medium (B0) produced the best vegetative performance, particularly for plant height and stem diameter. Specifically, the interaction of 100 mL/L RWW and soil (S2B0) yielded the highest plant height of 35.60 cm at 4 weeks after transplanting. Furthermore, a significant interaction was observed in the generative phase, where 50 mL/L RWW combined with soil and rice husk charcoal (S1B2) achieved the highest productivity, reaching a fruit weight of 158.00 g and 11.33 fruits per plant. These findings suggest that integrating 50 mL/L RWW with porous media is the most effective strategy for optimizing tomato yield